Financial, Commercial, and Mortgage Mathematics and Their Applications, Revised and Updated Edition. - Prakash, Arun (ABC-CLIO, 2014)
Ideal for college students in intermediate finance courses, this book uniquely applies mathematical formulas to teach the underpinnings of financial and lending decisions, covering common applications in real estate, capital budgeting, and commercial loans.